Fabrication of Pd/MnFe2O4 bifunctional 2-D nanosheets to enhance the yield of HCOOH from CO2 cathodic reduction paired with anodic oxidation to CH3OH. (1st March 2022) - Bharath, G.; Hai, Abdul; Rambabu, K.; Kallem, Parashuram; Haija, Mohammad Abu; Banat, Fawzi; Theerthagiri, Jayaraman; Choi, Myong Yong
Graphical abstract: Highlights: An electrochemical process for CO2 reduction and CH3 OH oxidation has been analyzed. Pd/MnFe2 O4 exhibits a high CO2 RR activity with 476 μmol h −1 cm −2 yield of HCOOH. Anodic oxidation of CH3 OH is used to tune the catalytic HCOOH yield. CO2 reduction units are integrated into fuel cells to allow pollutant discharges to be zero. Abstract: Highly active and stabilized bifunctional electrocatalysts contributed to the reduction of hazardous atmospheric pollutants through paired electrochemical reactions. Herein, spherical-like Pd nanoparticles were successfully grown on two-dimensional MnFe2 O4 nanosheets (2-D Pd/MnFe2 O4 NSs) via microwave irradiation and tested in an electrochemical cell as dual-functional hybrid electrode material. Several characterization techniques were used to determine the morphological, structural and chemical properties of the as-prepared bifunctional Pd/MnFe2 O4 electrocatalysts. The 2-D Pd/MnFe2 O4 NSs exhibited a higher specific surface area of 390 m 2 g −1 with a pore volume of 0. 327 cm 3 g −1, resulted in a high CO2 reduction activity (CO2 RR) towards the desired production of formic acid. The HCOOH yield was optimized by varying the cell potential, electrolyzer reaction time, and electrolyte concentration. The maximum yield of HCOOH was found to be 476 μmol h −1 cm −2 with a Faradic efficiency of (FE) 96.9%. Furthermore, CO2 RR was coupled with CH3 OH oxidation reaction (CH3 OH OR) to evaluate the paired electrochemical activity of the bifunctional Pd/MnFe2 O4 electrocatalysts. The results showed that Pd/MnFe2 O4 had a high production rate of HCOOH of about 625 µmol h −1 cm −2 with FE of 97.5% at −1.0 V vs. RHE in optimized electrolyzer concentrations. During CH3 OH OR, many H + and e − were formed, which is the key to increasing HCOOH yield through the paired electrolyzer. The mechanism of the paired electrochemical reaction was also described in detail. This study showed that integrated future bifunctional fuel cells utilizing CH3 OH combined with CO2 reduction strategies, could achieve zero gas exhaust emission and sustainably produce high value-added chemicals.